Possible ecological risk of two pharmaceuticals diclofenac and paracetamol demonstrated on a model plant Lemna minor - Kummerová, Marie; Zezulka, Štěpán; Babula, Petr; Tříska, Jan (Journal of hazardous materials, 2016)
Lemna minor is often used in environmental risk assessment and it can be supposed that usually evaluated parameters will be reliable even for assessing the risk of pharmaceuticals. Subtle changes in duckweed plant number, biomass production, and leaf area size induced by 10-day-exposure to diclofenac (DCF) and paracetamol (PCT) (0.1, 10, and 100 μg/L), excepting 100 μg/L DCF, are in contrast with considerable changes on biochemical and histochemical level. Both drugs caused a decrease in content of photosynthetic pigments (by up to 50%), an increase in non-photochemical quenching (by 65%) and decrease in relative chlorophyll fluorescence decay values (by up to 90% with DCF). Both DCF and especially PCT increased amount of reactive nitrogen and oxygen species in roots. DCF-induced effects included mainly increased lipid peroxidation (by 78%), disturbation in membrane integrity and lowering both oxidoreductase and dehydrogenase activities (by 30%). PCT increased the content of soluble proteins and phenolics. Higher concentrations of both DCF and PCT increased the levels of oxidised ascorbate (by 30%) and oxidised thiols (by up to 84% with DCF). Glutathion-reductase activity was elevated by both pharmaceuticals (nearly by 90%), glutathion-S-transferase activity increased mainly with PCT (by 22%). The early and sensitive indicators of DCF and PCT phytotoxicity stress in duckweed are mainly the changes in biochemical processes, connected with activation of defense mechanisms against oxidative stress.
Keywords: reaktivní formy dusíku; Paracetamol; diklofenak; Antioxidants; reaktivní formy kyslíku; Stress, Physiological; Risk Assessment; Reactive Nitrogen Species; fyziologický stres; Lipid Peroxidation; fotosyntéza; antioxidancia; Reactive Oxygen Species; Acetaminophen; hodnocení rizik; Photosynthesis; biologické markery; Oxidative stress; Lemna minor; Diclofenac; paracetamol; Antioxidant mechanism; Biomarkers; Magnoliopsida; peroxidace lipidů